2003
DOI: 10.1097/01.ju.0000079761.56154.e5
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Androgen Receptor Protein Expression in Men With Clinically Localized Prostate Cancer

Abstract: AR protein expression was 22% higher in the benign prostate and 81% higher in the CaP of black African compared with white men. CaP may occur at a younger age and progress more rapidly in black than in white men due to racial differences in androgenic stimulation of the prostate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 15 publications
9
92
0
Order By: Relevance
“…Consistent with the in vitro studies showing increased activity of the AR product with shorter AR CAG and GGN repeat alleles, studies have also found increased AR protein expression levels in prostatic tissues from men of African descent (Gaston et al 2003;Olapade-Olaopa et al 2004). Specifically, AR protein expression levels were estimated to be 22% higher in benign prostate cancer tissues and 81% higher in malignant prostate cancer tissues in African Americans versus Caucasian Americans (Gaston et al 2003).…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Consistent with the in vitro studies showing increased activity of the AR product with shorter AR CAG and GGN repeat alleles, studies have also found increased AR protein expression levels in prostatic tissues from men of African descent (Gaston et al 2003;Olapade-Olaopa et al 2004). Specifically, AR protein expression levels were estimated to be 22% higher in benign prostate cancer tissues and 81% higher in malignant prostate cancer tissues in African Americans versus Caucasian Americans (Gaston et al 2003).…”
Section: Introductionsupporting
confidence: 73%
“…Studies comparing the distribution of allele sizes for the CAG and GGN microsatellite repeat polymorphisms between different populations have noted shorter repeat lengths, on average, in men of African versus Caucasian descent (Kittles et al 2001;Esteban et al 2006). Consistent with the in vitro studies showing increased activity of the AR product with shorter AR CAG and GGN repeat alleles, studies have also found increased AR protein expression levels in prostatic tissues from men of African descent (Gaston et al 2003;Olapade-Olaopa et al 2004). Specifically, AR protein expression levels were estimated to be 22% higher in benign prostate cancer tissues and 81% higher in malignant prostate cancer tissues in African Americans versus Caucasian Americans (Gaston et al 2003).…”
Section: Introductionmentioning
confidence: 59%
“…14 Finally, increased androgen activity among black men was suggested by a study which found that benign and malignant prostate tissue from black men had both a greater number of cells staining positive for the androgen receptor as well as more intense staining within positive cells. 15 Although androgens regulate cellular PSA production they also affect prostate size. 16 Therefore, higher androgenicity among black men would be expected to result in larger sized prostates.…”
Section: Discussionmentioning
confidence: 99%
“…[34] AR protein expression was evaluated in malignant and benign prostate tissue from African Americans and Caucasian Americans who underwent radical prostatectomy for clinically localized CaP. [35] Archived radical prostatectomy specimens obtained from 25 Caucasian Americans and 25 African Americans had AR protein antigen retrieved and immunostained. AR protein expression from CaP and benign tissue was assessed using two methods.…”
Section: Androgen Receptor and Racial Differences In Prostate Cancermentioning
confidence: 99%